COVID-19 vs. Smallpox: The role of media on the responses to pandemics - Combow, Jessica (SFU Health Sciences Undergraduate Journal, 2022)
Historically, pandemics garner four responses: (1) denial and delayed response, (2) rumours of disease origin (usually foreign), (3) the wealthy escape, and (4) outbursts of violence and rebellion (Lanphear, 2021). Mass media has the power to catalyze these responses to pandemics, both negatively and positively.